Retrospective evaluation of patients admitted to the intensive care unit due to obstetric reasons in terms of maternal near-miss, a five-year case-control study - Özgür Erdem; Süleyman Cemil Oğlak; İzzettin Toktaş; Seher Baydemir; Ahmet Yosunkaya; Ali Erdem (BMC Pregnancy and Childbirth)
Abstract Background Maternal Near-Miss (MNM) has become globally recognized as an indicator of pregnancy, birth and the first 42 days of postpartum care services. The World Health Organization has taken a new approach to detail and better analyze maternal deaths. The clinic-based criteria to evaluate maternal care and the quality of related care services have been developed. Methods This is a retrospective case-control study that was conducted in a tertiary hospital. In the study, the medical files of all patients admitted to the intensive care unit during the five-year period between 2018 and 2022 were examined. All patients who met the MNM criteria of WHO during pregnancy, birth and puerperium were included in the case group of the study. Meanwhile, the participants in the control group were selected from mothers who gave birth in the same hospital between August 15 and October 31, 2023 and did not develop any complications during puerperium, using the systematic sampling method. Data collection was performed using an interviewer-administered structured questionnaire and data abstraction. Results In this five-year period, 198 mothers were diagnosed with MNM. In our study, the prevalence of MNM was found as 218/100.000. The most common laboratory changes that met the MNM criteria were elevated lactate levels (38.89%), acidosis (24.24%) and acute thrombocytopenia. Patients were most frequently admitted to the intensive care unit due to hemorrhage (23.74%), placental abruption (18.18%), pre-eclampsia (15.66%) and cesarean Sect. (10.10%), respectively. The frequency of co-morbidities (Diabetes mellitus, Hypertension, Asthma, Hypothyroidism, etc.) in patients diagnosed with MNM (n = 48; 26.67%) was found to be 5.5 times that of the control group (n = 25; 6.20%) (p < 0.001). Conclusions It can be said that co-morbidities directly affect the course of motherhood. the education level and family income were found higher in the MNM group compared to the control group. In this regard, the results of our study differ from the studies in the literature in terms of the effects of the education level of mothers and the economic status of families. The effects of socioeconomic and cultural factors on MNM may vary.